2017
DOI: 10.1007/s00410-017-1429-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of monticellite–forsterite and merwinite–forsterite symplectites in the CaO–MgO–SiO2 model system: influence of temperature and water content on microstructure evolution

Abstract: Homogeneous single crystals of synthetic monticellite with the composition Ca 0.88 Mg 1.12 SiO 4 (Mtc I) were annealed in a piston-cylinder apparatus at temperatures between 1000 and 1200• C , pressures of 1.0-1.4 GPa, for run durations from 10 min to 24 h and applying bulk water contents ranging from 0.0 to 0.5 wt% of the total charge. At these conditions, Mtc I breaks down to a fine-grained, symplectic intergrowth. Thereby, two types of symplectites are produced: a first symplectite type (Sy I) is represente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
(52 reference statements)
1
7
0
Order By: Relevance
“…If the same mechanisms formed lamellae and patches, the thin lamellae followed the broader patches during cooling because diffusion as the kinetically controlling factor is the more sluggish the lower the temperature is. This resembles the negative correlation of rod size and lamellae spacing in symplectites with their formation temperature (Joanny, van Roermund, & Lardeaux, 1991; Remmert et al, 2018).…”
Section: Discussionsupporting
confidence: 53%
“…If the same mechanisms formed lamellae and patches, the thin lamellae followed the broader patches during cooling because diffusion as the kinetically controlling factor is the more sluggish the lower the temperature is. This resembles the negative correlation of rod size and lamellae spacing in symplectites with their formation temperature (Joanny, van Roermund, & Lardeaux, 1991; Remmert et al, 2018).…”
Section: Discussionsupporting
confidence: 53%
“…It is suggested that the frequently observed change of characteristic inter-granular spacing (and size) of the symplectite phases correlates positively with the temperature of symplectite formation. Remmert et al (2018) presented experimental evidence corroborating this view and argued that the characteristic spacing of symplectite phases is small at low temperatures, whereby symplectite formation tends to be diffusion controlled. The characteristic spacing becomes larger at higher temperatures, whereby diffusion is more efficient, and symplectite formation becomes interface reaction controlled.…”
Section: Compositionmentioning
confidence: 72%
“…It has been argued by Remmert et al (2018) that symplectite formation only occurs in a rather narrow window of bulk water contents. Whereas the formation of symplectites is hampered in completely dry systems, a Garben microstructure with little spatial organization is formed at high water contents.…”
Section: Synthesismentioning
confidence: 99%
“…4h; 5c) and the modeled symplectite forming reactions in both domains suggest that Ti was not mobile beyond the volume of the initial titanite grain. However, the lamellar intergrowth of Ilm-Cpx 2 does support that Ti was locally mobile in the scale defined by the interlamellar space (Abart et al 2012;Remmert et al 2018) between Ilm lamellae. The interlamellar space between the lamellar ilmenite rods ranges from ~2-55µm in Domains I and II.…”
Section: Mobility Of Chemical Species During the Formation Of Ilm-cpx...mentioning
confidence: 91%